4. ULTRASONOGRAPHY CHARACTERISTICS OF 54 PATIENTS UNDER 4 MONTHS OLD SUSPECTED OF BILIARY ATRESIA AND UNDERWENT OPERATION AT THE NATIONAL HOSPITAL OF PEDIATRIC (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the characteristics of ultrasonography images of 54 patients under 4 months old with symptoms suspected of cholestasis and underwent the operation at the National Hospital of Pediatrics from January 2021 to May 2023. Methods: A cross-sectional study was carried out on 54 patients under 120 days old suspected of cholestasis and had the final diagnosis of biliary atresia or not due to exploratory surgery associated with cholangiogram and had pathology results diagnosis. All patients had been performing conventional and Doppler ultrasonography, Elastography due to BA protocol pre-operation. Results: 39/54 cases were diagnosed with BA Average age of BA is 63 days; boy/girl = 1.17; direction Bil 107 µmol/l; direction Bil/ indirection Bil = 59%; average GGT is 629 UI/l. 6/39 patients of BA group (15%) have not gall bladder; 27/39 patients have gall bladder length
Keywords: Biliary atresia, ultrasonography, elasto graphy, doppler ultrasonography.